Inflation and Relative Price Variability - Parks, Richard W. (Journal of Political Economy, 1978)
The paper develops a natural measure of the amount of relative price variability. The variance of relative price change is shown to be correlated with the rate of change in the price level using data for consumer goods in both the Netherlands and the United States. This association has been noted in other data for a variety of countries. Using a multisectoral supply-and-demand framework, the paper goes on to show how changes in relative prices and ultimately the variance of relative price changes are related to supply conditions changes in real income and the amount of unanticipated inflation. The model is used as the basis for an analysis of movements in the prices of consumer goods in the United States for the period 1929-75. The amount of unanticipated inflation (measured as the difference between the actual rate and a time-series predictor) is a more important determinant of relative price variability than the rate of inflation.